<span>given that P(x) --->p(x+6)+3
</span>
∴ x will become x+6
and P(x+6) will become P(x+6)+3
<span />
So, The graph of [p(x+6)+3] will be the same as the graph of [p(x)] but shifted 6 units to the left then shifted 3 units up
OR by another words, we need to make axis translations from (0,0) to (-6,3)
Answer:
Step-by-step explanation:
i Don't now how to explain the answer
Here is one way to solve for x.
Step 1) 2x^2-7=9
Step 2) 2x^2-7+7=9+7
Step 3) 2x^2=16
Step 4) (2x^2)/2=16/2
Step 5) x^2=8
Step 6) sqrt(x^2)=sqrt(8)
Step 7) |x|=sqrt(8)
Step 8) x=sqrt(8) or x=-sqrt(8)
-------------------------------------
Below are explanations/reasons to each of the steps above.
Step 1) Original equation
Step 2) Add 7 to both sides
Step 3) Combine like terms
Step 4) Divide both sides by 2
Step 5) Simplify
Step 6) Apply the square root to both sides. The notation "sqrt" is shorthand for "square root"
Step 7) Use the rule that sqrt(x^2) = |x| for all real numbers x
Step 8) Use the rule that if |x| = k then x = k or x = -k for some fixed number k.
-------------------------------------
The two solutions are
x = sqrt(8) or x = -sqrt(8)
Answer:
x = {-2, 2/3}
Step-by-step explanation:
2x = -4
x = -2
3x = 2
x = 2/3
x = {-2, 2/3}